The Wisdom and Purpose of Prayer as a Ruler of Human Life - Ali Iimron; Anggi Eryana; Fathimah Bariyatul Azizah (Journal of Islamic Studies and Society, 2023)
Abstract: Worship is one of the obligations that must be carried out by everyone. Even though everyone has different beliefs in choosing each religion and carrying out all their worship. In carrying out the prayer also has demands and also obligations and conditions so that prayer becomes valid and can also be accepted by Allah SWT. As for the things that must be done during prayer and when things that cancel the prayer are done, the prayer is considered invalid. This writing method was compiled using data and information collection methods by tracing relevant literature review sources by searching for reliable reference sources through electronic media and also the internet.(Sari, 2019). As for the arguments that will govern prayer services and also the wisdom of praying, one of them is to purify oneself from sin. So that prayer must always be carried out because it is mandatory and will be the first practice that will be reckoned on on the last day.